Automatic Procedures for the Safety Assessment of Stand-alone Masonry Arches. Issue 9 (2nd September 2022) - Zizi, Mattia; Cacace, Daniela; Rouhi, Jafar; Lourenço, Paulo B.; De Matteis, Gianfranco
ABSTRACT: In the context of the structural safety evaluation of masonry arches under both gravitational and seismic loads, this study analyses the possibility to apply fast-assessment methodologies, aimed at defining intervention priorities through the proposal of typological abacuses . With this aim, two automatic VBA (Visual Basic for Application) procedures have been implemented and adopted to estimate the capacity of six configurations (from semi-circular to pointed) of stand-alone masonry arches to withstand vertical loads, and to calculate the horizontal load multiplier, related to the in-plane seismic capacity. The developed subroutines are based on the Uniqueness Theorem of Limit Analysis, so that a static and a kinematic approach have been adopted, respectively, for the estimation of the maximum vertical load, compatible with the geometric features, and the evaluation of the horizontal capacity. Subsequently, both procedures have been applied to a wide range of arches by means of a parametric study. The results thus obtained allow the definition of typological abacuses for the preliminary safety assessment of the investigated structural types.